2020
DOI: 10.3390/pr8020129
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Dimensional Analysis on a C-H2 Smelting Reduction Furnace with Double-Row Side Nozzles

Abstract: Higher requirements for steel smelting technology have been put forward based on the increasing awareness of energy conservation and environmental protection. In the field of iron making, carbon reduction processes are often used. In this study, molten iron was smelted by designing a C-H2 smelting reduction method. Although previous researchers have studied this through a large number of physical and numerical simulations, they have not yet refined general laws from the perspective of dimensional analysis. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Alternative ironmaking technologies have also been developed and some are analyzed in this Special Issue. Xie et al [16] carried out water modeling experiments to study the mixing time in a smelter as a function of nozzle position, nozzle diameter, nozzle immersion depth, gas flow rate, and liquid properties. Applying dimensional analysis, the authors derive expressions for the mixing time and compare the results with practical findings.…”
Section: Iron Smeltingmentioning
confidence: 99%
“…Alternative ironmaking technologies have also been developed and some are analyzed in this Special Issue. Xie et al [16] carried out water modeling experiments to study the mixing time in a smelter as a function of nozzle position, nozzle diameter, nozzle immersion depth, gas flow rate, and liquid properties. Applying dimensional analysis, the authors derive expressions for the mixing time and compare the results with practical findings.…”
Section: Iron Smeltingmentioning
confidence: 99%
“…Serg et al [22] studied the effect of the converter inclination on the mixing time and the jet penetration length with a side-blown water model and found that the penetration length is shown to be independent of the inclination angle, and the mixing time was affected by the intensified wave motion at the interface caused by the inclination of the vessel. Xie et al [23,24] conducted a physical simulation of the three-phase flow behavior of gas-liquid-slag in a C-H 2 iron bath furnace and studied the effects of factors such as the flow rate and angle of the double-row side lances, and the position where the tracer was added on the average residence time and obtained the expression between the mixing time and the dimensionless group through multiple linear regression. The experimental verification shows that the calculated value positively correlates with the experimental value.…”
Section: Introductionmentioning
confidence: 99%